Evaluation of the efficiency of psychoeducation in the structure of rehabilitation of patients with alcohol dependence - Kozhyna, Hanna; Lytvynenko, Vasyl (ScienceRise: Medical Science, 2018)
Aim of the research: to develop and evaluate the effectiveness of psycho-educational programs in the system of psychosocial rehabilitation of patients with alcohol dependence. Materials and methods: the study carried out a complex clinical-psychopathological and psycho-diagnostic examination of 150 male patients from 20 to 55 years old, who, according to the diagnostic criteria of ICD-10, had alcohol dependence syndrome. The main group (whose patients took part in the psycho-educational program) consisted of 105 people. The control group included 45 patients who received standard regulated therapy in the hospital. Results of the study: during the work, a system of rehabilitation of patients with alcohol dependence with the use of psycho-education was developed and tested. The main strategy includes a complex impact on the cognitive, emotional, psycho-physiological, behavioral and social aspects of alcohol dependence. The main goal of psycho-education is the formation in alcohol addicts of an adequate understanding of narcological disorders and involvement in adequate participation in rehabilitation activities. The algorithm of psycho-education of patients with alcohol dependence was developed, and it aims to increase the level of special (narcological) knowledge of the patient and his family; the development of skills for solving life problems and includes the training of communication skills; training of coping skills. Against the background of the psycho-educational program in the rehabilitation system of patients with alcohol dependence, there is a positive dynamics of mental status, a positive transformation of coping strategies in patients of the main group that included psycho-education into the traditional complex of rehabilitation measures, which significantly exceeds the corresponding changes in the control group. When analyzing the duration and quality of remission, it was established (in 6 months): in 70.1 % of the examined main group, complete remission of alcohol dependence was observed compared with 41.5 % of patients in the control group; incomplete remission, respectively, in 26.2 % and 49.1 % of those surveyed; steady alcohol abuse in 3.7 % of the examined primary and 9.4 % of the control group. Conclusions: 1. The system of psycho-educational effects in the rehabilitation of men with alcohol dependence should include four modules: raising the level of special (narcological) knowledge of the patient and his family; the development of skills in solving life problems, the training of communication skills; coping skills training. 2. We established expressed positive dynamics of mental status, high quality of remission, positive transformation of coping strategies in patients of the main group who included psycho-education into the traditional complex of rehabilitation measures, which significantly exceeds the corresponding changes in the control group